السياحة المسؤولة حل نموذجي لتفشي السياحة المفرطة-دراسة حالة مدينة برشلونة خلال الفترة 2018-2023: responsible tourism a model solution to the outbreak of overtourism - a case study of Barcelona city during the period 2018-2023 - عيايشية زعرة,; قادة قدور بن عباد, (Journal of North African Economies, 2025)
This research paper aims to address a very sensitive and important topic that has received widespread media resonance in the Western and Arab world alike, which is the phenomenon of excessive tourism that is widespread in a number of European countries such as Venice, Venice, Paris, and others, and which the World Tourism Organization has warned of expanding its spread to affect all countries. Countries of the world as the year 2030 approaches, and our study focused on examining the Spanish city of Barcelona, where the phenomenon has become increasingly widespread recently, after emerging from the Covid-19 crisis, as a global response to the state of quarantine, the complete closure of airports and ports, and the imposition of social distancing to overcome the crisis. What was the reason for encouraging the Catalan city “Barcelona” to adopt a responsible tourism approach as an exemplary and strategic solution to reduce the negative effects left by excessive tourism on this unique tourist destination with eternal landmarks.